2021
DOI: 10.7554/elife.72082
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome activation leads to cDC1-independent cross-priming of CD8 T cells by epithelial cell-derived antigen

Abstract: The innate immune system detects pathogens and initiates adaptive immune responses. Inflammasomes are central components of the innate immune system, but whether inflammasomes provide sufficient signals to activate adaptive immunity is unclear. In intestinal epithelial cells (IECs), inflammasomes activate a lytic form of cell death called pyroptosis, leading to epithelial cell expulsion and the release of cytokines. Here we employed a genetic system to show that simultaneous antigen expression and inflammasome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 82 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…Microparticles released by pyroptosis have been found to divert inflammatory mediators, regulate interactions between various cells, and lead to endothelial cell damage and macrophage infiltration [ 52 ]. Inflammasome-mediated pyroptosis also occurs in intestinal epithelial cells, and the cross-presentation of intestinal epithelial-derived antigens with CD8 + T cells also depends on this process [ 53 ]. Therefore, we speculated that macrophages and CD8 + T cells are interdependent with pyroptosis and may contribute to tumor induction and development.…”
Section: Discussionmentioning
confidence: 99%
“…Microparticles released by pyroptosis have been found to divert inflammatory mediators, regulate interactions between various cells, and lead to endothelial cell damage and macrophage infiltration [ 52 ]. Inflammasome-mediated pyroptosis also occurs in intestinal epithelial cells, and the cross-presentation of intestinal epithelial-derived antigens with CD8 + T cells also depends on this process [ 53 ]. Therefore, we speculated that macrophages and CD8 + T cells are interdependent with pyroptosis and may contribute to tumor induction and development.…”
Section: Discussionmentioning
confidence: 99%
“…These prior studies on mechanisms of antigen acquisition have been performed with either soluble antigens or enteric pathogens, such as Salmonella, that breach the intestinal barrier and may not be relevant to Cryptosporidium. However, a recent study that utilized mice in which enterocytes express an ovalbumin-flagellin fusion protein found that activation of the inflammasome to induce cell death promoted cross presentation of SIINFEKL by DCs to prime CD8 + T cells 47 . It is relevant to note that the NLRP6 inflammasome has an important role in innate resistance to Cryptosporidium 48 , but whether this contributes to antigen presentation during Cryptosporidium infection is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The innate immune system can counteract intracellular bacterial pathogens by inducing programmed cell death ( Williams, 1994 ). Programmed cell death eliminates the intracellular pathogen niche, maintains epithelial barrier integrity, promotes clearance of damaged cells, and enhances presentation of foreign antigens to cells of the adaptive immune system ( Deets et al, 2021 ; Doran et al, 2020 ; Jorgensen et al, 2017 ; Koch and Nusrat, 2012 ; Yatim et al, 2017 ). Three main modes of programmed cell death are common to mammalian cells: pyroptosis, apoptosis, and necroptosis.…”
Section: Introductionmentioning
confidence: 99%